National Medical Examination 2012 rating-associated factors in UNMSM interns - Arenas Significación, Fernando Ricardo (2014)
Introduction: The National Medical Examination is a tool that measures knowledge and clinical reasoning as an approach to assess educational quality. Objective: To determine factors associated with qualification of the National Medical Examination (ENAM) 2012 at Universidad Nacional Mayor de San Marcos (UNMSM). Design: Cross-sectional study. Setting: Faculty of Human Medicine, UNMSM, Lima, Peru. Participants: Medical Interns 2012. Interventions: Analysis of secondary sources using the binary logistic regression method. Pearson and Spearman correlation coefficients and Student t test were applied. Main outcome measures: ENAM’s average scores, belonging to the 2006 class, internship hospital, and merit rank according to weighted university average (PPU). Results: Belonging to the 2006 incoming class, doing internship at EsSalud, and be placed in the academic upper and middle third were factors associated with better score at the national exam of medicine. Conclusions: Belonging to the 2006 class, hospital of internship, and merit rank were factors associated to a score of thirteen or more at the national exam of medicine 2012.